Outcome of COVID-19 Infection in vaccinated and unvaccinated adults admitted to Patan Hospital, Nepal - Shrestha, John; Sah, Mukesh Kumar; Singh, Bishnu Mohan; Upreti, Nishan; Maskey, Sujina; Jha, Ashish; Dhital, Bibek; Rana, Bandej; Pandey, Bimal; Shrestha, Ashis (Journal of Patan Academy of Health Sciences, 2022)
Introduction: The vaccine has a positive impact on reducing the severity of COIVD-19 disease-course and studies have projected 50-90% protection against severe disease. Our study aimed to find the difference in disease severity outcomes between RT-PCR positive vaccinated and unvaccinated individuals. Method: This cross-sectional study was carried out among 417 COVID-19 cases who were admitted from June 2021 to August 2021. Collected data were fed into Microsoft-excel and analyzed using SPSS software, version- 16.0. Frequency, percentage, mean and standard deviation were calculated for descriptive analysis. To find out the association of categorical variables, Chi-square test or Fisher’s Exact test was used where appropriate. P-value <0.05 was considered significant. Result: Out of 417 cases, 23(5.5%) were fully vaccinated i.e. 10(2.4%) with Covishield and 13(3.1%) with Vero Cell, 48(11.5%) partially vaccinated i.e. 19(4.6%) with Covishield, and 29 (6.9%) with Vero Cell and 346(83%) unvaccinated. 343(82.25%) admitted patients were discharged and 74(17.75%) died during our study period. The disposition of the patient was statistically significant (p<0.001) and found more mortality among unvaccinated cases. There was a statistical difference between the requirement of ICU admission (p=0.032) among vaccinated and unvaccinated cases. The Absolute Risk Reduction (ARR) of mortality and requirement of ICU after complete vaccination with respect to unvaccinated COVID-19 patients was 14.11%(5.14%-23.73%) and 20.50%(8.02%-32.97%) respectively at 95% CI. Conclusion: Vaccination reduces Mortality, the requirement of ICU, and oxygen requirement among COVID-19 cases with respect to unvaccinated COVID-19 cases.